Advances in the methodological approach to friction period estimation: A European perspective. (November 2020) - Hanly, Paul; Ortega Ortega, Marta; Pearce, Alison; Soerjomataram, Isabelle; Sharp, Linda
Abstract: The friction cost approach (FCA) estimates the productivity costs of disease from an employer's perspective but the lack of estimates of friction periods in different countries limits its use. Our aim was to use labour market aggregates to generate two alternative estimates of the friction period for European countries and to apply the FCA to illustrate the impact on cancer-related lost productivity costs. We included thirty countries (EU 27 + the United Kingdom, Switzerland and Norway). Base-case Method 1BC used annual Dutch vacancy stock and flow data (2001–2019) to estimate friction periods for this country. A regression model was employed using Dutch data and country-specific vacancy and unemployment rates to generate country-specific friction period estimates for the other 29 countries. Alternative Method 2ALT used country-specific newly occupied jobs as a proxy vacancy flow variable and vacancy stock data to generate friction period estimates. These were applied, within the FCA, to premature cancer mortality data (from GLOBOCAN2018) for all cancers combined for Western European countries. Costs are in €2018. Method 1BC estimated friction periods in 2018 ranged from 70.8 days for Greece to 145.9 days for the Czech Republic, with a mean duration of 95.3 days. Method 2ALT produced a mean friction period of 80.0 days. On average, across countries, Method 2ALT friction periods were 15.4 days (−18.5%) shorter than Method 1BC estimates. Friction period estimates over the last decade were shorter than those for 2018 reflecting lower vacancy rates. Total cancer premature mortality costs according to FCA Method 1BC amounted to €1.0 billion in 2018 for Western Europe compared to €0.99 billion for Method 2ALT . We developed two alternative – and viable - methods to estimate country-specific friction periods. These approaches will enable researchers to apply the FCA to estimate the productivity cost of diseases across Europe from an employer's perspective. Highlights: Lack of country-specific friction periods limits use of the Friction Cost Approach. Paper presents two new methods with data to estimate friction periods across Europe. New methods can be applied to alternative settings and updated over time. Resulting estimates valuable for researchers estimating productivity cost of diseases.